Cytomegalovirus Central Nervous System Compartmentalization in a Patient Presenting with AIDS. Issue 3 (April 2015) - Trentalange, Alice; Calcagno, Andrea; Raviolo, Stefania; Prochet, Adolfo; Audagnotto, Sabrina; Ghisetti, Valeria; Perri, Giovanni Di; Bonora, Stefano
Cytomegalovirus (CMV) central nervous system involvement is uncommon and hardly diagnosed because it can mimic many different conditions. We here present a case of an HIV-positive patient with neurological signs and symptoms (headache, asthenia, confusion, hallucinations, ataxia) with concurrent opportunistic diseases (neurotoxoplasmosis, disseminated Kaposi's sarcoma, disseminated CMV infection). CMV CNS involvement was not initially considered given the observed multiple comorbidities: antiviral treatment duration was probably not adequate given the end-organ disease. Concomitantly, plasma CMV DNA was undetectable while cerebrospinal fluid viral load was 31, 340 copies/ml. Ganciclovir treatment followed by oral valganciclovir maintenance was associated with the slow disappearance of symptoms, the improvement of MRI images and the persistent undetectability of CMV DNA. The case here reported highlights the challenges of diagnosing CMV encephalitis in HIV-positive patients (with several cerebral comorbidities), the incomplete knowledge of the appropriate treatment for such a disease and the possibility of CMV replication in the cerebrospinal fluid despite undetectable plasma CMV DNA.